Ekstrak Jeruk Nipis Sebagai Obat Terapi Penyembuhan Penyakit Gastritis dengan metode GC-MS - Khairul Pahmi Rahmawati; Diah Miftahul Aini; Winda Harnianti (Journal of Pharmaceutical and Health Research, 2023)
Gerd or comonly known as gastritis deseas occure due to inflamation of the gastric mucosa. Drug consumption is no longer safe for the reason of side effect for long term ingestion. Thus, herbal medicine is starting become an option, by employing lime juice for medication or theraphy. Previous study indicated positive response of lime extract for medication on mice. However, the mechanism is yet to be discovered. This study aims to determine the chemical compounds contained in lime extract that responsible for antiulcer activity. The research was carried out in laboratory experimental method, by phytochemical screening than continued by GC-MS. The result shows that lime juice containaing secondary metabolits, namely alkaloid, glycosides, triterpenoid, saponin, polyphenol, flavonoid and phenol that act as an anty-oxidants as well as inductors for formation of stemp cell. Furthermore, GC-MS analysis showed that the presence of citric acid derivatives in the form of citraconic anhindrat, itaconic anhindrat and Itaconic acid, last but not least palmitic acid as part of fatty acid. Citric acid is a compound that has a cappability to be a buffer solution. Therefore, consuming lime juice for gerd medication will help neutralised acidity of the gastric with the principle of buffer solution.